2019
DOI: 10.1371/journal.pone.0225552
|View full text |Cite
|
Sign up to set email alerts
|

Diet and feeding strategy of Northeast Atlantic mackerel (Scombrus scomber) in Icelandic waters

Abstract: Predator-prey relations, as well as the trophic ecology of highly migratory marine species, is important to understand their impact on the ecosystem. Conventional methods were used to study the diet composition and feeding strategy of the Northeast Atlantic mackerel (Scombrus scomber), during their summer feeding migration to Icelandic waters in 2009–2014. In addition, generalised additive modelling (GAM) was used to determine which biological and environmental factors contribute to the variation of their stom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Mackerel showed a generalist feeding strategy with the largest values for species richness and Shannon diversity in spring, and diverse prey sizes consumed in winter, in agreement with several previous studies (e.g. Debes et al 2012, Utne et al 2012, Bachiller et al 2016, Óskarsson et al 2016, Kvaavik et al 2019. This study has shown the importance of appendicularians in the diet of mackerel in the Celtic Seas ecoregion in spring and winter, which as such may be non-coincidental consumption, as reported in the Norwegian Sea (Prokopchuk & Sentyabov 2006, Langøy et al 2012, Bachiller et al 2016.…”
Section: Diet Composition and Overlap Of Juveniles And Adults (Non-la...supporting
confidence: 92%
“…Mackerel showed a generalist feeding strategy with the largest values for species richness and Shannon diversity in spring, and diverse prey sizes consumed in winter, in agreement with several previous studies (e.g. Debes et al 2012, Utne et al 2012, Bachiller et al 2016, Óskarsson et al 2016, Kvaavik et al 2019. This study has shown the importance of appendicularians in the diet of mackerel in the Celtic Seas ecoregion in spring and winter, which as such may be non-coincidental consumption, as reported in the Norwegian Sea (Prokopchuk & Sentyabov 2006, Langøy et al 2012, Bachiller et al 2016.…”
Section: Diet Composition and Overlap Of Juveniles And Adults (Non-la...supporting
confidence: 92%
“…The size range sampled (with full stomachs) in the present study (> 20cm) possibly prevented us to identify macrozooplankton as an essential part of hake diet, as this species shows an ontogenic change in diet (Velasco and Olaso, 1998), with only juveniles smaller than 19 cm being planktivores. Salps and anchovies were the main prey for Atlantic mackerel and Atlantic chub mackerel, in contrast to that observed in other studies where decapods, krill, copepods or blue whiting were the most important food source (Cabral and Murta, 2002;Olaso et al, 2005;Kvaavik et al, 2019). Olaso et al (2005) however reported salps as important source of food for Atlantic mackerel in late summer-autumn in the BoB.…”
Section: Discussioncontrasting
confidence: 69%
“…These are useful indices to rank prey importance since they take into account both numerical and weight-based importance to the diet. Some authors favor GII [58][59][60], others favor IRI [61][62][63] and some %PSIRI [64,65], while some doubt the merits of all such combined indices (see [44] and references therein). Here, each method was used to examine only the ranking of prey types, because the three combined index values are not directly comparable.…”
Section: Discussionmentioning
confidence: 99%